Emotions under Discussion: Gender, Status and Communication in Online Collaboration - Daniela Iosub (619015) (2014)
Background Despite the undisputed role of emotions in teamwork, not much is known about the make-up of emotions in online collaboration. Publicly available repositories of collaboration data, such as Wikipedia editor discussions, now enable the large-scale study of affect and dialogue in peer production. Methods We investigate the established Wikipedia community and focus on how emotion and dialogue differ depending on the status, gender, and the communication network of theeditors who have written at least 100 comments on the English Wikipedia's article talk pages. Emotions are quantified using a word-based approach comparing the results of two predefined lexicon-based methods: LIWC and SentiStrength. Principal Findings We find that administrators maintain a rather neutral, impersonal tone, while regular editors are more emotional and relationship-oriented, that is, they use language to form and maintain connections to other editors. A persistent gender difference is that female contributors communicate in a manner that promotes social affiliation and emotional connection more than male editors, irrespective of their status in the community. Female regular editors are the most relationship-oriented, whereas male administrators are the least relationship-focused. Finally, emotional and linguistic homophily is prevalent: editors tend to interact with other editors having similar emotional styles (e.g., editors expressing more anger connect more with one another). Conclusions/Significance Emotional expression and linguistic style in online collaboration differ substantially depending on the contributors' gender and status, and on the communication network. This should be taken into account when analyzing collaborative success, and may prove insightful to communities facing gender gap and stagnation in contributor acquisition and participation levels. Other Information Published in: PLOS ONE License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1371/journal.pone.0104880